TMIC-68. EVALUATING FLASH AND CONVENTIONAL DOSE-RATE RADIATION AND IMMUNE RESPONSE WITH SINGLE-CELL SEQUENCING IN DIFFUSE MIDLINE GLIOMA (DMG). (14th November 2022) - Minns, Hanna; Padilla, Oscar; Wei, Hong-Jian; Webster-Carrion, Andrea; Tazhibi, Masih; McQuillan, Nicholas; Zhang, Xu; Yeh, Rebecca; Zhang, Zhiguo; Szalontay, Luca; Pavisic, Jovana; Garty, Guy; et al.
Abstract: Diffuse Midline Glioma – H3K27M mutant (DMG), is a fatal and inoperable pediatric brain tumor with limited treatment options as radiation provides only temporary reprieve, leaving the median survival between 9-15 months. Conventional dose-rate radiation (2Gray/minute, CONV) has been shown in other cancers to recruit an immune component, however, this has not been studied in DMG. Ultra-high dose-rate radiation given at 90 Gray/second (FLASH), is a novel technique associated with decreased toxicity and effective tumor control. Using a syngeneic model of brainstem DMG, we performed single-cell RNA sequencing on CD45+ immune cells isolated from tumors irradiated with 15Gray using FLASH or CONV, and compared to unirradiated tumor and normal brainstem. Isolation of 33, 308 immune cells revealed 17 unique clusters, most abundant of which was microglia (73.8%), present in four distinct subtypes representing a spectrum from homeostatic to activated. In the most activated microglia, both FLASH and CONV showed an enrichment in type 1 interferon (IFN1) pathway scores compared to untreated tumors (p< 0.001 and p< 0.001, respectively). The most differential response was found in macrophages (MAC) and dendritic cells (DC) with a robust enrichment of IFN1 pathway scores for CONV compared to FLASH (p< 0.001, MAC and p< 0.001 DC). FLASH showed an increase in anti-inflammatory MAC markers such as Mrc1, Cd163, and Maf and an enrichment of myeloid-derived suppressor cell (MDSC) signature in monocytes, not seen in CONV (p< 0.001). Finally, we correlated our data with publicly available single-cell data taken from the cerebrospinal fluid of DMG patients treated with anti-GD2 CAR T Cell therapy and found similar inflammatory markers characteristic of our unirradiated murine tumors. In summary, our work is the first to study immune alterations comparing different dose-rates of radiation with single-cell resolution in DMG, highlighting the potential for combining radiation and immunotherapy in these tumors.